If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 7 = 6 + m Combine like terms: -9 + 7 = -2 -2 = 6 + m Solving -2 = 6 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -2 + -1m = 6 + m + -1m Combine like terms: m + -1m = 0 -2 + -1m = 6 + 0 -2 + -1m = 6 Add '2' to each side of the equation. -2 + 2 + -1m = 6 + 2 Combine like terms: -2 + 2 = 0 0 + -1m = 6 + 2 -1m = 6 + 2 Combine like terms: 6 + 2 = 8 -1m = 8 Divide each side by '-1'. m = -8 Simplifying m = -8
| r-3=6-9-8 | | -8p+4+9p=6 | | 9x+4=2x+34 | | 2D+5=9 | | 2x+8=3x-15 | | 6=12+9d | | 4x-6=3x+3 | | 4x=3x-3 | | 4-5y+12+16y=-6y-18 | | 4x-6=6x+3 | | 12x-2(4x-8)=28 | | 84(x+1)=(85+x)(x-1) | | 6(8-5x)+4=x+12 | | 2y-2=-1-2y | | 6y-1=2y+8 | | x=6x^2-9x | | 17y-19y= | | 2r+3s+12t=28 | | -4y-15=9y+11 | | 3x^2+11x-25=0 | | y(x-5)= | | x^2-22x+113=1 | | x^2-16x+48=33 | | -5x+45=11x+21 | | 3(3y-1)-3(2y)=1 | | 4(5+x)=44 | | x^3-5x=12 | | x^3-5=12 | | 5(y-3)=2y-27 | | 4+9z-2=7z+51-5z | | 124-2d=628 | | 24x^4+66x^3+36x^2= |